2020
DOI: 10.3389/fevo.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Diurnal Patterns of Singing Activity Between Urban and Rural Great Tits

Abstract: Human settlements and activities alter the natural environment acoustically and visually. Traffic noise and street lights are two of the most prominent pollutants which may affect animal activity patterns. Birds in urban areas have been reported to sing nocturnally and to have an earlier dawn chorus compared to their rural counterparts. However, few studies have measured whether singing more at night or earlier in the morning means singing less during daytime. It is therefore unclear whether they shift or exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…7.11b;Sáncez-Pérez et al 2013;Vidović et al 2017). Birds near international airports in Spain, for example, were found to advance their dawn chorus to reduce overlap with aircraft sound (Gil et al 2015), which is a common response to noise for urban species (Bermúdez-Cuamatzin et al 2020). However, common chiffchaffs (Phylloscopus collybita) near airports in the UK and the Netherlands were found to sing songs with a lower maximum and peak frequency than conspecifics in nearby control areas, thus resulting in an increased overlap with aircraft sound (Wolfenden et al 2019).…”
Section: Anthropophonymentioning
confidence: 99%
“…7.11b;Sáncez-Pérez et al 2013;Vidović et al 2017). Birds near international airports in Spain, for example, were found to advance their dawn chorus to reduce overlap with aircraft sound (Gil et al 2015), which is a common response to noise for urban species (Bermúdez-Cuamatzin et al 2020). However, common chiffchaffs (Phylloscopus collybita) near airports in the UK and the Netherlands were found to sing songs with a lower maximum and peak frequency than conspecifics in nearby control areas, thus resulting in an increased overlap with aircraft sound (Wolfenden et al 2019).…”
Section: Anthropophonymentioning
confidence: 99%
“…Among the reported structural changes is the increase in song frequency (e.g., [14,[18][19][20]; but see [21,22]), the increase in the sound pressure level (loudness) of the song [17,23,24], and changes in the repertoire [15,25]; but see [22]. The most frequently reported temporal changes are those related to schedule adjustment that allows birds to avoid the noisiest periods [26,27]; but see [28][29][30] in relation to the effect of light pollution timing on bird songs.…”
Section: Introductionmentioning
confidence: 99%
“…City road networks have become suitable study sites for assessing the impact of traffic noise on birds, which to date has been assessed mainly in big cities but not near highways outside of cities. Bermúdez-Cuamatzin et al (2020) have shown conclusively that Great Tits (Parus major) in urban and rural areas differ in the timing of their singing activity: the dawn chorus starts earlier in the city, and thereafter there is less singing activity in urban streets than in rural woodland. This confirms the early rise in cities, as reported for many bird species and sometimes attributed to traffic noise during daytime, to artificial light at night, or both.…”
Section: Introductionmentioning
confidence: 99%